The Implementation of Green Financing as an Alternative Sustainable Financing for MSMEs in Gorontalo - Luqmanu Hakiem Ajuna; Vany Rolliyta Ansir; Muhammad Nur; Nurain Kude; Tenti Dehi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Green financing is a type of capital assistance program or funding scheme that is available to environmentally conscious business owners. Borrowers or business owners must meet the 3R criteria in order to be eligible for funding assistance under the green finance plan, according to government regulations (reduce, reuse, recycle). The Gorontalo Province is utilizing green funding to assist MSMEs in raising awareness of the importance of environmental protection. The purpose of this study is to determine the outcomes of using green financing as a different idea of sustainable funding for businesspeople in the province of Gorontalo, specifically MSME actors. It is also to learn more about what needs to be done as a first step toward future improvements. The methodology used in the study is qualitative. Secondary data is data obtained from a secondary source after primary research data has been sourced. When conducting research, researchers use websites (Websites) associated with research in addition to secondary sources. The study's findings indicate that using green financing in place of sustainable financing falls under the unfavorable category. Due to the fact that many MSME owners are unaware of the Green Funding scheme, its application for financing in the UMKM Gorontalo province is currently ineffective. . Keywords: Green Financing, Financing, and MSMEs